Implementation of Islamic Values in Strengthening Doctor's Professionalism for Students of Medical Faculty, Universitas Muslim Indonesia - N F, Khalid; I D, Kartika; I, Royani; A A, Irwan; S, Mokhtar (International Journal of Human and Health Sciences (IJHHS), 2024)
Objectives: In this study the application of section 2 of the Islamic Discipline of Medicine, including tahsinul qiraah (Holy Quran) Al-Fatihah, memorizing verses and selected prayers as well as behavior showing Islamic adab to patients served by medical students with the criteria of being served for 2 x 24 hours was observed. Methods: This was a descriptive study, using quantitative data. A total of 24 medical students were sampled. The assessment form for the first and second components used summative assessment by listening to the reading of Al-Fatihah and memorization of selected verses by paying attention to the makhrajul letters and tajwid. Then for the third component, a questionnaire method was used which was filled in by the patient and his family. The aim of conveying the success from this program is to show that a person undergoing medical education who is known to be very busy with activities can also carry out da'wah during their schedule and still continue to study religious knowledge to apply in daily life. Results: In the tahsinul qiraah component of Holy Qur’an Al-Fatihah there are 71% in the Mumtaz category and 29% in the ahsan category. In the memorization component and selected verses, there were 75% in the mumtaz category and 25% in the ahsan category. In the behavioral component showing Islamic adab to patients, there are 58% who often do it and 42% who sometimes do it. These behaviors include greeting patients and their accompanying families, showing friendliness and sincerity such as shaking the patient's hand, stroking the back, stroking the head, and etc. Conclusion: In the three aspects of assessment, two components have been achieved well, are Tahsin Al-Fatihah and memorizing selected surah such as verses on the creation and development of human life, worship and health, meal and beverage, but Islamic etiquette in medical services can be improved. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S61